Optimizing resistance training for sprint and endurance athletes: balancing positive and negative adaptations - Van Hooren, B.; Aagaard, P.; Blazevich, A. J. (Sports Medicine, 2024)
Resistance training (RT) triggers diverse morphological and physiological adaptations that are broadly considered beneficial for performance enhancement as well as injury risk reduction. Some athletes and coaches therefore engage in, or prescribe, substantial amounts of RT under the assumption that continued increments in maximal strength capacity and/or muscle mass will lead to improved sports performance. In contrast, others employ minimal or no RT under the assumption that RT may impair endurance or sprint performances. However, the morphological and physiological adaptations by which RT might impair physical performance, the likelihood of these being evoked, and the training program specifications that might promote such impairments, remain largely undefined. Here, we discuss how selected adaptations to RT may enhance or impair speed and endurance performances while also addressing the RT program variables under which these adaptations are likely to occur. Specifically, we argue that while some myofibrillar (muscle) hypertrophy can be beneficial for increasing maximum strength, substantial hypertrophy can lead to macro- and microscopic adaptations such as increases in body (or limb) mass and internal moment arms that might, under some conditions, impair both sprint and endurance performances. Further, we discuss how changes in muscle architecture, fiber typology, microscopic muscle structure, and intra- and intermuscular coordination with RT may maximize speed at the expense of endurance, or maximize strength at the expense of speed. The beneficial effect of RT for sprint and endurance sports can be further improved by considering the adaptive trade-offs and practical implications discussed in this review.